Exploring technology roadmapping practices in Malaysia - Yee, Choy Leong; Yeo, Chiu Mui (2012)
This research aims to explore the practice of technology roadmapping (TRM) in Malaysia. Managers from a total of 11 firms were interviewed and follow by an in-depth study in a firm. The interviews have revealed that the use of TRM in Malaysia is limited. These findings signal a strong ignorance of the dramatic impact technologies have on organizations among businesses operating in Malaysia. The findings from an in-depth interview showed that TRM has been effectively implemented by a firm. It also has enabled many technology roadmaps to be developed for identifying new technological research areas in future.